PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KREATIVITAS SISWA DI SMAN 1 SINGKIL UTARA PADA MATERI BIOTEKNOLOGI - Dayani, Asti; Zamzami, Zamzami; Maulida, Maulida (Jurnal Dedikasi Pendidikan, 2025)
This research aims to determine the increase in creativity of students at SMA Negeri 1 Singkil Utara through the application of the project based learning model on biotechnology material. This research was conducted at SMA Negeri 1 Singkil Utara in february 2024, and the population in this study was class X, totaling 104 students. The sampling technique in this study used a saturated sampling technique where all members of the population were sampled. Of the 4 existing classes, 2 classes were determined as samples where 1 class was taught using the project based learning model and video as the control class and 1 class was taught using project based learning models, videos and practicums as experimental classes. This research is a non-equivalent control group design type of quasi-experimental research (non-equivalent group pretest-posttest design). Data were analyzed using t-test. The results of the research show that based on statistical tests the project based learning model cannot increase the creativity of SMAN 1 Singkil Utara students in biotechnology material (t-count = 0.89 < t-table = 1.68), whereas based on the data the project based learning model increases SMAN 1 Singkil Utara students’ creativity in biotechnology material was only 5.94%.